Analysis of Blood Request Form and Blood Utilization Pattern in a Tertiary Care Specialized Hospital - Quader, Md Abdul; Islam, Quazi Tarikul (Bangladesh Journal of Medicine, 2022)
Background: The growing demands for blood products are vital resources to health care facilities. If requested blood is not transfused, this causes blood wastage. Minimal utilization of requested blood squanders technical time, reagent and imposes extra expenses on patients. This study was conducted to evaluate blood requisition and utilization pattern in a tertiary care hospital. Methods: This retrospective study was conductedin the transfusion medicine dept. of a tertiary care specialized hospital from1 January 2017 to 31 December 2020. Blood request forms were reviewed and blood utilization indices were computed from blood bank registries. Blood utilization was calculated determining cross match to transfusion ratio (C:T), transfusion probability (%T), transfusion index (TI) and non-utilization pattern i.e. wastage. Results: A total of 9,841 recipients were requested to prepare cross match. A total of 13,965 units of blood were cross matched and among these 10316 units were transfused to 9,291 recipients. The overall C:T, %T, and TI were 1.35, 94.41% and 1.05 respectively. The wastage implying in this study was 26.13%. Conclusion: The overallblood utilization was encouraging, but excessive cross matching with minimal transfusion practice was observed implying wastage of blood. Blood transfusion services should adopt blood conserving policies. Bangladesh J Medicine 2022; 33: 259-262